On-chip integration of metasurface-doublet for optical phased array with enhanced beam steering - Wang Zhizhang; Ji Jitao; Ye Xin; Chen Yuxin; Li Xueyun; Song Wange; Fang Bin; Chen Ji; Zhu Shining; Li Tao (Nanophotonics, 2023)
Optical phased array (OPA), as a promising beam steering technology, however, usually suffers from a narrow field of view (FOV) that limits its performances in applications. A miniaturized compact strategy to enlarge the beam steering angle is quite desirable for the solid-state OPA technique. Here an on-chip metasurface-doublet is proposed to offer angle magnification integrated with a port-selected optical phased array. It is implemented by combing convex and concave metalenses with the quadratic phase distribution, which is precisely integrated on the OPA chip by layer-by-layer fabrication process. Here, the OPA is fabricated in Lithium Niobate on Insulator (LNOI) platform. Our experiments show that the metasurface-doublet is able to achieve 1.54 times FOV amplification in a horizontal direction and with >41% working efficiency. Our results provide a feasible approach to achieve enlarged FOV for wide-angle beam steering and also imply a powerful platform in developing integrated multilayer metasurface devices.